Effect of Trainee Participation on Operative Times in Strabismus Surgery - Eldib, Amgad A.; Pihlblad, Matthew S. (Journal of Academic Ophthalmology, 2022)
Introduction This study aimed to describe the difference in operative time during strabismus surgery in the presence and absence of a trainee with the operating physician.Methods This is a retrospective chart review of pediatric patients who underwent strabismus surgery by three surgeons from January 2016 through September 2019. Electronic medical records were reviewed and noted for operative times as well as the presence or absence of a trainee (postgraduate year [PGY]-3 ophthalmology resident, PGY-5 pediatric ophthalmology fellow, or both).Results The average time needed for a two-horizontal muscle recession by all the three surgeons in the absence of a trainee averaged at 35.7 minutes (range: 24–48). This is increased by 34% in the presence of a trainee with an average of 47.88 minutes (range: 20–81) with a p-value < 0.001. Similar comparisons were performed for a two-horizontal muscle recession in addition to bilateral inferior oblique weakening procedures for two surgeons. On average, in the absence of a trainee, this required an average of 61.9 minutes for completion with an increase of 31.8% with the participation of a trainee requiring 81.56 minutes.Discussion The presence of trainees, whether residents or fellows, is a crucial component of medical education and training. It is important for their learning and helps develop strong future surgeons. However, this may increase surgical procedure times and affect the efficiency of the primary surgeon. This has important implications for surgical scheduling, surgical time utilization, and surgical productivity of those involved in trainee education.Conclusion The presence of a trainee with a primary surgeon, although crucial to surgical training, may result in significant prolongation of strabismus surgical times.
Keywords: operative times; strabismus surgery; trainee; nonocular surgeries